Brackish water: an option for producing hydroponic Capsicum annuum in laminar flows of mineral nutrients - Santos da Conceição, Adailton; Gomes da Silva, Mairton; Luiz Boechat, Cácio; Sampaio Chagas, Denize; De Sousa Mendes, Wanderson (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 147-155)